2023
DOI: 10.3389/fmed.2023.1213889
|View full text |Cite
|
Sign up to set email alerts
|

Updates in SJS/TEN: collaboration, innovation, and community

Madeline E. Marks,
Ramya Krishna Botta,
Riichiro Abe
et al.

Abstract: Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis (SJS/TEN) is a predominantly drug-induced disease, with a mortality rate of 15–20%, that engages the expertise of multiple disciplines: dermatology, allergy, immunology, clinical pharmacology, burn surgery, ophthalmology, urogynecology, and psychiatry. SJS/TEN has an incidence of 1–5/million persons per year in the United States, with even higher rates globally. One of the challenges of SJS/TEN has been developing the research infrastructure and coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 137 publications
0
10
0
Order By: Relevance
“…SJS and TEN are rare severe cutaneous adverse drug reactions mediated by cytotoxic T cells (mainly CD8+). There is extensive epidermal necrosis and detachment, with mucocutaneous complications ( 49 , 50 ). SJS and TEN differ only along a spectrum of severity based on percentage of body surface area detached (<10% in SJS; 10%–30% in an overlap SJS/TEN; and >30% in TEN) ( 49 ).…”
Section: Severe Cutaneous Adverse Reactions (Scar) In Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…SJS and TEN are rare severe cutaneous adverse drug reactions mediated by cytotoxic T cells (mainly CD8+). There is extensive epidermal necrosis and detachment, with mucocutaneous complications ( 49 , 50 ). SJS and TEN differ only along a spectrum of severity based on percentage of body surface area detached (<10% in SJS; 10%–30% in an overlap SJS/TEN; and >30% in TEN) ( 49 ).…”
Section: Severe Cutaneous Adverse Reactions (Scar) In Childrenmentioning
confidence: 99%
“…Hsu et al reported an incidence rate of 5.3 and 0.4 cases per million children for SJS and TEN, respectively, with an equal incidence between male and female children ( 51 ). In children, as in adults, drugs are the most frequent triggers of SJS/TEN ( 49 , 50 ). Common culprit medications are sulfa antibiotics, AED, and NSAIDs ( 49 ).…”
Section: Severe Cutaneous Adverse Reactions (Scar) In Childrenmentioning
confidence: 99%
See 3 more Smart Citations